Hands in the dark: Palaeolithic rock art in Gorham’s Cave (Gibraltar) - Simón-Vallejo, María D.; Cortés-Sánchez, Miguel; Finlayson, Geraldine; Giles-Pacheco, Francisco; Rodríguez-Vidal, Joaquín; Calle Román, Lydia; Guillamet, Eudald; Finlayson, Clive (SPAL - Revista de Prehistoria y Arqueología, 2018)
The work in the inner area of Gorham’s Cave, Gibraltar, has added to the Palaeolithic art located in the cave. Although work continues on the surveying and the study of the evidence found up to now, we present here a preview consisting of a representation of a red deer, and also a hand stencil, alongside numerous marks which have been found scattered throughout the inner cave. In this paper we present new data on the Upper Palaeolithic rock art in Gorham’s Cave (Gibraltar) including direct dating of a hand stencil. Situating this dating in the archaeological context of the stencil, we conclude that it is associated with the Solutrean technocomplexe. This is particularly significant in the light of recent reviews which put European hand stencils in the context of the Early or Initial Upper Palaeolithic. In this context, the Gorham data opens the discussion on the systematic chronological correlation of all hands in negatives of European Palaeolithic rock art.